Hydrological approaches to measure or estimate crop water use – A theoretical background - Ferreira, Maria Isabel (2023)
Hydrological methods are used to retrieve actual evapotranspiration (ETa) as an alternative to micrometeorological techniques. This approach consists in performing the mass balance at a well-defined control volume. Despite the apparent theoretical simplicity of these methods, it is very common to witness their incorrect use, due to the lack of consistency in the definition of their terms by different authors, not only in measurements but also and mainly in common estimations for irrigation scheduling. Therefore, this article aims to review the main concepts and basic definitions of the hydrological methods, especially in the context of irrigation applications in climates with dry summer. The main topics addressed consist of: i) Mass balance and control volume; ii) Soil water thresholds for engineering applications; iii) Evapotranspiration or its components as output variables of water balance equation; iv) Applications of the water balance equation using actual evapotranspiration as input variable. This article is meant as a didactic text in the field of irrigation and drainage to support the learning of concepts related to the water balance. It also includes a set of application exercises to improve the comprehension of this subject.